Modernizing China's military : progress, problems, and prospects - Shambaugh, David L. (University of California Press, 2002)
David Shambaugh, an international authority on Chinese strategic and miltary affairs, offers a comprehensive assessment of the Chinese military. He addresses important questions about Chinese strategic intentions and military capabilities.